System samogłoskowy współczesnej kaszubszczyzny północno-zachodniej - Jocz, Lechosław (Slavia Occidentalis, 2015)
This article is dedicated to the vocalism of the contemporary Żarnowiec dialect (spoken in Wierzchucino and Nadole). On the one hand, an acoustic and phonetic analysis has identified certain phonetic archaisms (like the central or frontal and central pronunciation of /u/) and has aided in-depth descriptions of sounds previously referred to in a very imprecise way (*/aː/ pronounced as a near-close rounded vowel, central, [ɵ] type). On the other hand, the analysis has provided grounds for acknowledging the important phonetic changes which have occurred in the Kashubian dialect in the past few decades; some of these consist in completing specific phenomena. These include the general dissemination of the diphthongal pronunciation of stressed /e, o, ɛ, ɔ/, the highly back and rounded pronunciation of /ɒ/, the front and open pronunciation of /æ/ in Nadole and the extended scope of the phonological and phonetic reduction of non-stressed vowels (the phonemes /ɘ̟, ɛ, æ/ are always, /ɵ, e/ nearly always and /i/ is relatively rarely pronounced in the same way when not stressed). The result of this reduction is a distinctly centralized vowel or a central vowel of the [ɜ] type. From the phonological point of view, attention should be paid primarily to the ultimate loss of nasal vowel phonemes. Contrary to existing descriptions, the vocal continuant */ã/ has not been merged phonologically with /e/ but a new oral phoneme /ɘ̟/ has been established. It is worth emphasizing that a majority of the identified changes do not bring the dialect closer to the Polish language, rather, they take it further away from it.